Detailed Simulation of Single-Bounce Capillaries for Various X-Ray Sources - Shao, Shangkun; Li, Huiquan; Yuan, Tianyu; Zhang, Xiaoyun; Hua, Lu; Sun, Xuepeng; Liu, Zhiguo; Sun, Tianxi (Frontiers in Physics, 2022)
In order to draw a high-quality single-bounce capillary (SBC) to meet various applications, there is an increasing demand for detailed simulations of the SBC. In this paper, a code based on ray-tracing method was developed to simulate the SBC in detail for various X-ray sources to optimize their performances by considering such factors as attenuation, coating, spot size of X-ray source, intensity distribution of X-ray source, energy distribution of X-ray source, surface shape error, centerline error, surface roughness and absorption edge. This code has monochrome and polychrome modes which were usually used to simulate the mono-energetic and poly-energetic performances of the SBC.